2018
DOI: 10.1038/s41380-018-0104-7
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione and glutamate in schizophrenia: a 7T MRS study

Abstract: In schizophrenia, abnormal neural metabolite concentrations may arise from cortical damage following neuroinflammatory processes implicated in acute episodes. Inflammation is associated with increased glutamate, whereas the antioxidant glutathione may protect against inflammation-induced oxidative stress. We hypothesized that patients with stable schizophrenia would exhibit a reduction in glutathione, glutamate, and/or glutamine in the cerebral cortex, consistent with a post-inflammatory response, and that thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
102
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(132 citation statements)
references
References 52 publications
14
102
1
Order By: Relevance
“…Glu is the primary excitatory neurotransmitter in the adult human brain. The reduction of Glu in the pathological trajectory of patients with psychosis, including those with FEP, has been reported by multiple groups (7,9,11). Although there are reports that compared brain metabolite levels between young and aged populations (34), we believe that this study is the first to report that a longitudinal change in young adulthood occurs in healthy subjects.…”
Section: Glusupporting
confidence: 52%
See 1 more Smart Citation
“…Glu is the primary excitatory neurotransmitter in the adult human brain. The reduction of Glu in the pathological trajectory of patients with psychosis, including those with FEP, has been reported by multiple groups (7,9,11). Although there are reports that compared brain metabolite levels between young and aged populations (34), we believe that this study is the first to report that a longitudinal change in young adulthood occurs in healthy subjects.…”
Section: Glusupporting
confidence: 52%
“…Tesla (T) MRS offers a more precise measurement of metabolite levels (4)(5)(6). To date, there have only been a handful of 7T MRS studies using either first episode psychosis (FEP) (7) or schizophrenia (SZ) patients (8)(9)(10)(11)(12)(13). However, all of these studies were cross-sectional and most of them used a fairly small number of subjects.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that glutamatergic abnormalities may be prominent in the early stages of psychotic illness (Merritt et al 2016, Kumar et al 2018), and that these may be key in driving pathophysiology of illness, predictive processing dysfunction, and psychopathology (Corlett et al, 2009 & 2011; Sterzer et al 2018). We did not find a significant relationship between glutamate levels in the anterior cingulate cortex and the strength of the perceptual and cognitive priors across all participants.…”
Section: Discussionmentioning
confidence: 99%
“…Higher field strength has greater sensitivity, enabling greater separation of glutamate and glutamine peaks, and allowing for more accurate quantification. Two studies in first‐episode patients have shown reduced glutamate concentrations in the anterior cingulate cortex, while another only found this in a subset of patients with predominantly negative symptoms. No difference has been observed in several other investigations.…”
Section: Glutamatementioning
confidence: 91%